On Some Solvable Difference Equations and Systems of Difference Equations - Stevo Stević; Josef Diblík; Bratislav Iričanin; Zdeněk Šmarda (Abstract and Applied Analysis)
Here, we give explicit formulae for solutions of some systems of difference equations, which extend some very particular recent results in the literature and give natural explanations for them, which were omitted in the previous literature.